CBIR for MR and CT images / Wong Chung Hiong - Wong, Chung Hiong (2005)
Image analysis has gained popularity in the medical field as there are many illnesses which require X-rays, Computerized Tomography (CT) scans and Magnetic Resonance (MR) images in order to enable accurate diagnosis of diseases, physician education and future research. The images collected through CT scans and MR imaging techniques require a database for efficient storage, search and retrieval. Medical image indexing, storage and retrieval based on image content arc an important feature of image database system. This thesis explores the ability of Content-based image Retrieval (CBIR) as a retrieve method and development in the domain of medic imaging. Content-based image retrieval (CBIR) refers to the ability to retrieve image on the basis of image content. Query by Image Content (QBIC) tool in IBM DB2 UDB will be use to apply this queries technique. In order to query the image by content in QBIC. first must create QBIC catalog for the images to catalog the images (adding entries for the images to the catalog and storing values for image features). then built a query to retrieve the image. The CBIR technique will be an indispensable component of images database.